We got a taste for protest! leadership transition and political opportunities for protest in Angola’s resilient authoritarian regime - Almeida, C.; Sá, A. L.; Faria, P. (Popular protest, political opportunities, and change in Africa, 2022)
The protest boom in the African continent since 2011 has spanned different political regimes, including resilient authoritarian regimes. In this chapter we contribute to the study of protests in authoritarian states by exploring the political opportunities for protest arising from leadership change in Angola. We argue that the unprecedented transition of leadership at the top of the Angolan state in 2017 changed political opportunity structures and this led to an exponential increase in protests. We consider four variables when explaining this surge in protest: the new leader's openness to protest, the nonfulfillment of electoral pledges, the government's use of repression, and the protesters' perceptions of the political regime. President João Lourenço's initial openness together with the expectations rose, but not fulfilled by his administration created momentum for protest. These political opportunities fostered a new cognitive frame among protesters: a growing taste for protest that has triggered other uprisings despite government repression. We contend that a focus on the cognitive mechanism, set in motion by changes in the political environment, will further our understanding of the transformative power of protests in authoritarian regimes.